Analysis of Squid Net Fisheries Business Production - Damayanti, Herna Octivia; Susilowati, Indah; Boesono, Herry (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Squid net is one of alternatives to replace trawl net in Pati regency. The purposes of the research are 1) to determine the influence factors, 2) to analyze the return to scale, 3) to analyze cost and return.The research location in Juwana Subdistrict particularly Bakaran Kulon, Dukutalit, Bajomulyo and Bendar Villages. The research conducted on October 2015 to June 2016. The number of final samples was 36, while the formulation of management strategies used 15 samples by snowball sampling. Data analysis techniques used 1) Cobb Douglas production function, 2) revenue-cost ratio analysis. The results of the research are 1) significant inputs for production factor are long trip, Solar fuel, the number of crew and lights. 2) the return to scale of squid net bussiness in Juwana subdistrict Pati regency is -0.231 means decreasing to scale. 3) the R/C ratio of scenario II more profitable for squid net crews thanÂ  scenario I.